Arunachal Pradesh Development Report Planning Commission Government of India New Delhi - Planning Commission (Planning Commission, 2005)
Rajiv Gandhi University was entrusted with the responsibility of preparing the Arunachal Pradesh Development Report by the Planning Commission, Government of India in August 2005. This is for the first time that any University in the country undertook such a task. Incidentally, this is the second milestone achieved by the University. It also prepared the Human Development Report in 2005. Both these initiatives were the result of my predecessors, Professors Kamal Kant Dwivedi and Atul Sharma. My special thanks are due to Prof.
Planning Commission Government of India
Planning Commission Government of India